Análise da correlação entre índices de controle vetorial, variavéis climáticas e coeficientes de incidência de dengue, zika e chikungunya no município de Ribeirão Preto, SP - Machado, Bruna dos Reis Santos (Universidade Federal de São Carlos, 2021)
Arboviruses have become a major public health problem due to emergence and reemergence worldwide. Climatic, socio-environmental and mobility factors favored the spread of both hosts, as well as vectors and etiologic agents of these diseases. The reduction of cases of these diseases consists of vector control, requiring an articulation between health services, especially Epidemiological Surveillance (VE) and Environmental Health Surveillance (VSA). This study aimed to analyze the correlation between vector control indexes, climatic variables and coefficients of incidence of dengue, zika and chikungunya in the city of Ribeirão Preto, SP. It is an ecological study, carried out in VE and VSA in Ribeirão Preto -SP. The data were collected through the analysis of the investigation forms referring to dengue, zika and chikungunya of the Information System on Notifiable Diseases (SINAN) in the years 2013 to 2019. The data related to entomological surveillance were obtained in the vector control reports of the Environmental Health Surveillance sector of the Municipal Health Secretariat. Data on temperature and precipitation were obtained from the online page of the Integrated Center for Agrometeorological Information (CIIAGRO). This research was approved by the UFSCar Research Ethics Committee (CEP). The data were analyzed using descriptive statistics. The relationship of the indices to the incidence of diseases was analyzed using Spearman's correlation coefficient (ρ). To analyze the relationship between the average monthly temperature and monthly precipitation with the incidence of diseases, a generalized linear model with negative Binomial distribution and identity link function was proposed. The results showed that in 2016, the IC for dengue was 5257.08 cases / 100,000 inhabitants, the IC for Zika was 153.62 cases / 100,000 inhabitants; and, in 2017, the IC for chikungunya was 6.45 cases / 100,000 inhabitants. No relationship was found between the IB, IP and IR and the CI of these arboviruses, with p> 0.05. The study also found no relationship between precipitation and IC for these arboviruses, p = 0.05. However, the relationship between temperature and dengue IC was confirmed, p <0.01, and it is possible to state that with each one-degree increase in temperature, it can increase 19.2 cases per 100,000 inhabitants. It is concluded that the results of this study can support the process of developing control strategies for Aedes aegypti based on the knowledge of the factors that influence its proliferation and educational strategies to enhance vector control and disease prevention.
Analysis of the correlation between vector control indexes, climate variables and dengue, zika and chikungunya incidence coefficients in the city of Ribeirão Preto, SP
Keywords: Arboviroses; Dengue; Zika; Vigilância epidemiológica; Vigilância em saúde ambiental; Epidemiological monitoring; Environmental health surveillance; CIENCIAS DA SAUDE::ENFERMAGEM